Women entrepreneurs: Motives, characteristics and outturn evidence from Mzumbe award - Swai, Eisaria (Mzumbe University, 2024)
A dissertation submitted to fulfillment of the requirements for the award of Master’s Degree of Business Administration (Corporate Management) of Mzumbe University